The Planning, Processing, And Evaluating The Online Tutorial In The Islamic Education Course - Imam Fitri Rahmadi (TADRIS: Jurnal Pendidikan Islam, 2018)
The online tutorial is one of the learning support services that support students to learn independently at distance learning. This study describes the planning, processing, and evaluating the online tutorial in the Islamic Education course at Universitas Terbuka. The methodology that is used in this study is the qualitative descriptive by case study. Data was gained from observations, interviews, and documentary study. The study found that (1) the planning of online tutorial was conducted by developing the tutorial activity planning, tutorial activity unit, and tutorial materials, (2) the process was conducted in 8 initiations that consisted of initializing materials, discussion, and task in the 3rd, 5th, and 7th initiations, and (3) the evaluation score was taken from some activities including discussions and task submissions. This research is limited to one semester with limited samples and general observations so that further research should investigate the same topic more deeply with more classes and semesters.